GAYA HIDUP BANGSAWAN LANGKAT (1900-1942) - Khairun Nisa; Novia Syahfitri; Muhammad Ade Fauzan; Abd Haris Nasution; Arfan Diansyah (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
This study aims to determine the lifestyle of the Langkat nobles from 1900 to 1942. To obtain the required data, the author collects data using the library study method. The results obtained from this study are the overview of the Malay royalty Langkat. The change of the lifestyle of nobles. At the leadership of Sultan Musa, the noble life ini the Langkat Sultanate is still simple. Next is the peak of the glory of this Langkat Sultanate is when Sultan Abdul Aziz is powerful. He replaced his father is Sultan Musa. Langkat nobles life there was little change in 1900-1942, because in the time was the transitional period of colonial parties. The Dutch colonial nation can be said to be the best time for Malay’s noble class. The results of revenue from the plantation concession of oil and mine oil, Sultan Langkat and the noble classes have privilaged and luxurious life.